Description of Learning Strategy in Practical Office Training in UPTD BLK Payakumbuh - Aldo Alam Budi; Solfema Solfema (Universitas Negeri Padang, 2019)
This research is motivated by the success of citizens learning in training at UPTD Payakumbuh BLK. This is suspected because the instructor uses a good learning strategy in learning activities. This study aims to see an overview of learning strategies seen from the aspects of organizing learning, delivery of learning content and classroom management. This research is a quantitative descriptive research. The population in this study were learning residents who were attending the practical office training at UPTD BLK Payakumbuh totaling 32 people. The sampling technique is stratified random sampling. Samples were taken as many as 26 samples. The technique and tool of data collecting used a questionnaire. The data was analyzed by using the percentage formula. The results showed that (1) the learning strategy in the aspect of organizing learning material was said to be very good, (2) the learning strategy in the aspect of delivering learning content was said to be good, and (3) the learning strategy in the aspect of classroom management was said to be very good.Keywords: Learning Strategies, Learning Outcomes